2022
DOI: 10.3390/su14106139
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Food Systems Governance to Achieve Multiple Objectives: A Comparative Instrumentation Analysis of Food Systems Policies in Vanuatu and the Solomon Islands

Abstract: Political leaders from around the world are demonstrating interest in adopting food policies that account for the economic, health, social and environmental dimensions of food. In the Pacific Islands, decades of experience in implementing multisectoral NCD and climate policy has indicated that operationalising food systems policies will be challenging. We aimed to identify opportunities for food systems sectors to more strongly promote nutrition and environmental sustainability in addition to economic objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 81 publications
1
28
0
Order By: Relevance
“…Fifth, this research impact assessment helps to implement a multidisciplinary approach to strengthening food policy by ensuring that epidemiology, health education, environmental health, trade and fiscal policy, and in general, food regulation and governance approaches are incorporated within SUPI. Previous research has shown that breaking down sectoral and disciplinary silos is critical for effectively strengthening food policy in PICs [ 1 , 18 23 , 39 , 40 ] and LMICs in general [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, this research impact assessment helps to implement a multidisciplinary approach to strengthening food policy by ensuring that epidemiology, health education, environmental health, trade and fiscal policy, and in general, food regulation and governance approaches are incorporated within SUPI. Previous research has shown that breaking down sectoral and disciplinary silos is critical for effectively strengthening food policy in PICs [ 1 , 18 23 , 39 , 40 ] and LMICs in general [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding points to the potential for intra-regional trade to contribute to food security through increased availability and affordability of staple foods and suggests an opportunity for other commodities. For example, addressing the high cost of protein (and low consumption) in some settings, while also generating economic opportunities for development through supporting local food industries within the region [ 46 ]. This would have an additional benefit of increasing food access in times of disaster, due to overall increased regional availability (particularly given the countries in the region are mainly net-food-importers).…”
Section: Discussionmentioning
confidence: 99%
“…Such policy initiatives would enhance knowledge on upcoming market opportunities and risks, while enabling affordable inter-country transportation of healthy imported foods. In addition to investment in local food production, Ministries of Agriculture across the region are highlighting the importance of increased policy focus on encouraging youth participation and entrepreneurship in agriculture [ 46 ]. This strategy would not only to help increase agricultural productivity and also reduce dependence on imported foods and thus increase food security, but also to deal with high rates of youth unemployment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The burden of malnutrition in Solomon Islands reflects the wider experience in the Pacific region and globally. It is clear that successfully tackling it will require strengthening policies to promote healthy food environments (Reeve et al, 2022). In order to develop policies and programs to address these complex issues, there is a need for contemporary and context-specific information relating to where food comes from and how it is sourced.…”
Section: Introductionmentioning
confidence: 99%